Fresno Superior Court Special En Banc In Memoriam Session in Jury Assembly Room - Watkins, Howard::::::::: (1987)
Lawrence Kennedy speaking at lectern; seated: Justice Hollis Best; Judges James Quaschnick, Dwayne Keyes, Ralph Nunez; Back row: Judges Nicholas Dibiaso, Mario Olmos, and John Fitch